INVESTIGATION ON DURABILITY OF EUCALYPTUS WOOD (E. INTERTEXTA R.T.BAKER) AGAINST TRAMETES VERSICOLOR L.EX - Habib alah Arab tabar firoz jaei (Regional Information Center for Science and Technology (RICeST), 2005)
In this study, durability of Eucalyptus wood(Eucalyptus intertexta R.T.Baker) in both treated with creosote and celcore and untreated to attack by Trametes versicolor (L.ex)L loyd. were evaluated heart wood by the Kolleshal methodes described in DIN 52176, and B.S. 838. The comparison of weight losses of samples were also evaluated and it showed that fungus had no effect on the treated samples but it caused 4% weight loss of natural durability samples. Based on this study, it can be concluded that E. intertexta wood can be classified as a durable wood.